2022
DOI: 10.1186/s13287-022-03001-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells: promising treatment for liver cirrhosis

Abstract: Liver fibrosis is a wound-healing process that occurs in response to severe injuries and is hallmarked by the excessive accumulation of extracellular matrix or scar tissues within the liver. Liver fibrosis can be either acute or chronic and is induced by a variety of hepatotoxic causes, including lipid deposition, drugs, viruses, and autoimmune reactions. In advanced fibrosis, liver cirrhosis develops, a condition for which there is no successful therapy other than liver transplantation. Although liver transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 116 publications
(131 reference statements)
0
14
0
Order By: Relevance
“…In the current study, we like to assess if curcumin preconditioning of MSCs can maintain this ameliorative effect and protect against return of the fibrosis which actually represent a critical challenge in use MSCs in therapy and still there is a controversy about the long term efficacy of stem cells, there many preclinical and clinical studies prove the reduction of liver fibrosis by MSCs injection [24][25][26] but maintaining its effect were achieved after many times of cell injection up to 9 injections in one experiment [27] and partially achieved in another studies [28][29] and not achieved at all in others [30][31]. So, we investigated the fibrosis degree on 12 th week and 24 th week of cell infusion and we found that no significant difference compared to that at 4 th week in cur + /nanoscaffold and this indicates that curcumin preconditioning of MSCs maintained the ameliorative effect of the primed MSCs and protected against the return of fibrosis compared to cur -/nanoscaffold which showed a return of fibrosis from 6.5% to 10.4% .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we like to assess if curcumin preconditioning of MSCs can maintain this ameliorative effect and protect against return of the fibrosis which actually represent a critical challenge in use MSCs in therapy and still there is a controversy about the long term efficacy of stem cells, there many preclinical and clinical studies prove the reduction of liver fibrosis by MSCs injection [24][25][26] but maintaining its effect were achieved after many times of cell injection up to 9 injections in one experiment [27] and partially achieved in another studies [28][29] and not achieved at all in others [30][31]. So, we investigated the fibrosis degree on 12 th week and 24 th week of cell infusion and we found that no significant difference compared to that at 4 th week in cur + /nanoscaffold and this indicates that curcumin preconditioning of MSCs maintained the ameliorative effect of the primed MSCs and protected against the return of fibrosis compared to cur -/nanoscaffold which showed a return of fibrosis from 6.5% to 10.4% .…”
Section: Discussionmentioning
confidence: 99%
“…Producing soluble factors, including TGF-β, PGE2, IDO, NO, and HGF, MSCs were able to inhibit the activation of T cells. MSCs can induce the transdifferentiation of CD4+ T cells into CD25+Foxp3+ regulatory T cells (Tregs) through the release of TGF-β ( 7 , 49 ). Studies have demonstrated that MSCs dramatically decreased the number of CD4+ T cells invading the liver, the proportion of activated CD4+ T lymphocytes, and the total concentration of Th1 cells, and subsequently induced regulatory DCs and Tregs in the liver to ameliorate liver damage ( 65 ).…”
Section: Mesenchymal Stem Cell Therapies For Liver Cirrhosis: Immune ...mentioning
confidence: 99%
“…Stem cell transplantation has emerged as the most promising treatment for liver fibrosis since the advent of regenerative medicine ( 7 9 ). Stem cells are a population of cells with self-renewal, proliferation, and pluripotent differentiation potential that can differentiate into multiple cell types under defined conditions ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from IBD, fibrosis is a common complication of various diseases, such as Idiopathic Pulmonary Fibrosis (IPF) ( 6 ), Chronic Kidney Disease (CKD) ( 7 ), Systemic Sclerosis (SSc) ( 8 ) and Chronic Liver Diseases (CLD) ( 9 ) and in all cases, a successful anti-fibrotic treatment is yet to be found. Regarding intestinal fibrosis, it is most commonly symptomatic in CD rather than in UC, and in some cases, its occurrence may lead to intestinal strictures, which are amenable only to excision ( 2 ).…”
Section: Introductionmentioning
confidence: 99%